Shift-Share Analysis of Local Economy’s Competitiveness: Case Study of the Varaždin-Koprivnica Region, Croatia - Braičić, Zdenko; Šlezak Hrvoje; Lončar Jelena (Geographica Pannonica, 2024)
This study researches local economy’s competitiveness in the Varaždin-Koprivnica Region (North-Western Croatia) in the period between 2009 and 2020. Shif t-share method has been used which measures the deviation between the regional development and the de- velopment of total national area and tends to explain whether it is the result of exogenous or endogenous conditions. Data on the number of employed people and Gross Value Added were used as points of reference for the competitiveness. The results showed the above av- erage regional development which is the result of the influence of endogenous or local con- ditions indicating that the region has competitive advantages. Manufacturing is the most competitive activity. The analysis revealed intra-regional disparities as well.